Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.145
|View full text |Cite
|
Sign up to set email alerts
|

Greedy spanners are optimal in doubling metrics

Abstract: We show that the greedy spanner algorithm constructs a (1+ )-spanner of weight −O(d) w(MST) for a point set in metrics of doubling dimension d, resolving an open problem posed by Gottlieb [11]. Our result generalizes the result by Narasimhan and Smid [15] who showed that a point set in d-dimension Euclidean space has a (1+ )-spanner of weight at most −O(d) w(MST). Our proof only uses the packing property of doubling metrics and thus implies a much simpler proof for the same result in Euclidean space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 19 publications
3
60
0
Order By: Relevance
“…We now show how to construct level-0 clusters and prove their invariant (I1). The construction is similar to the construction of BLW in [8]. Level-0 clusters are constructed by greedily breaking the MST into subtrees of diameter at least L 0 and at most 6L 0 .…”
Section: Light Greedy Spanners In the Euclidean Spacementioning
confidence: 99%
See 1 more Smart Citation
“…We now show how to construct level-0 clusters and prove their invariant (I1). The construction is similar to the construction of BLW in [8]. Level-0 clusters are constructed by greedily breaking the MST into subtrees of diameter at least L 0 and at most 6L 0 .…”
Section: Light Greedy Spanners In the Euclidean Spacementioning
confidence: 99%
“…Let K be the cluster graph where each vertex of K corresponds to an -cluster and each edge of K corresponds to a spanner edge connecting the two corresponding -clusters. Let ∆ K be the degree of K. BLW showed (Lemma 3.1 in [8]) that ∆ K ≤ −O(d) when the point set is in the metric of doubling dimension d using the packing argument. By adapting their proof to the point set in R d , we can derive the upper bound ∆ K ≤ O( −d ).…”
Section: Light Greedy Spanners In the Euclidean Spacementioning
confidence: 99%
“…In metrics of constant doubling dimension d, Borradaile, Le and Wulff-Nilsen [15] showed that greedy spanners have lightness −O(d) , improving upon previous lightness bounds by Smid [52] and Gottlieb [28]. In Section 6, we construct a spanner oracle with strong sparsity O( −d ).…”
Section: Other Applications Of Our Techniquesmentioning
confidence: 74%
“…In the lightness analysis of greedy spanners for Euclidean and doubling metrics [15,42], the authors implicitly used sparsity of the greedy spanner to bound the weight. We observe that their analysis can be turned into a non-greedy algorithm that explicitly uses sparse spanners to construct light spanners.…”
Section: Our Techniquesmentioning
confidence: 99%
See 1 more Smart Citation